Effectiveness of yoga as an adjunctive intervention for alleviating symptoms of fibromyalgia a narrative review - Daniek, Justyna; Kręcina, Filip; Kaczmarek, Weronika; Fitz, Emilia; Brzeźniak, Mikołaj; Gil, Kacper; Drelich, Krzysztof; Karbowniczek, Aleksander; Mokracka, Julia; Grabarczyk, Alicja (Quality in Sport, 2026)
Background. Fibromyalgia is a chronic syndrome characterized by widespread musculoskeletal pain, fatigue, sleep disturbance, cognitive complaints, and psychological distress. Pharmacological options have only modest effect sizes and are limited by adverse events. The 2017 revised European Alliance of Associations for Rheumatology (EULAR) recommendations gave a strong-for recommendation only to aerobic and strengthening exercise. Yoga, integrating physical postures, breath regulation and meditative attention, has been proposed as an adjunctive intervention. Aim. To synthesize PubMed-indexed evidence on whether yoga, used as an adjunct to standard care, has a clinically meaningful effect on symptoms of fibromyalgia. Material and methods. PubMed was searched up to April 2026 for randomized controlled trials (RCTs), pilot controlled trials, single-arm pilots and systematic reviews or meta-analyses on yoga in adults with fibromyalgia. Findings were interpreted against published MCID thresholds. Results. Two randomized controlled trials with active wait-list comparison, one randomized between-group comparison, several uncontrolled or single-arm pilots and five systematic reviews informed the synthesis. The Yoga of Awareness RCT reported a 31.4% improvement in FIQR total at end of an 8-week intervention, with reductions in pain, fatigue, and pain catastrophizing. Other trials reported smaller or mixed effects. Adverse events were uncommon and mild. Conclusions. The available evidence is limited to a small number of RCTs and several uncontrolled pilots, almost exclusively in women. Within this restricted evidence base, supervised gentle yoga programmes appear safe and may produce reductions in fibromyalgia impact and pain that approach or exceed published MCID thresholds. Yoga should therefore be considered an adjunct within a multimodal approach in which exercise remains the primary non-pharmacological intervention, not a substitute for guideline-recommended care.